Circular Dichroism in Study of Drug Chirality - G. N. Gildeeva; I. G. Smirnova (Антибиотики и Химиотерапия)
Verapamyl substance and market verapamyl were investigated with circular dichroism. It was shown that circular dichroism provided rapid and highly efficient determination of the optic isomers and could be recommended as a method for control of drug quality.